Link Between Irrational Beliefs and Important Markers of Mental Health in a German Sample of Athletes: Differences Between Gender, Sport-Type, and Performance Level - Michel-Kröhler, Alena; Turner, Martin J. (Frontiers in Psychology, 2022)
In this article, we conducted the first meaningful study of irrational beliefs (IBs) in a German sample of athletes. Moreover, we investigated associations between IBs and potential general as well as sport-specific markers of mental health in German athletes. As general markers, we considered psychological distress and well-being in addition to IBs, and as sport-specific markers, we considered anxiety, perfectionism, and athletic identity. To achieve this, our first step was to translate and validate a specific measure of irrational beliefs, namely the Irrational Performance Beliefs Inventory (iPBI). The iPBI is a performance-relevant measure that captures specific IB, taking into account the situational circumstances of the target population, namely operators in different performance context (academia, sports, business, medicine etc.). Its theoretical basis is largely Ellis’ work on rational and irrational beliefs. We developed a short and a long version of the iPBI, which both capture four core IB (i.e., demandingness, awfulization, low frustration tolerance and depreciation). Factorial validity was confirmed by a confirmatory factor analysis (comparative fit index = .92) with data from 234 athletes. Both versions of the newly developed iPBI showed good internal consistency (Cronbach’s alpha > .77) and retest reliability (interclass correlation coefficients > .71). Results of the correlational analyses indicated low positive relationships between IBs and athletes’ psychological distress, and low negative relations between IBs and well-being. In terms of sport-specific markers, there were low to moderate correlations with IBs. This study also examined the differences in IBs between females and males, individual and team sport athletes, and across three different performance levels. Implications of these findings are discussed along with approaches for future research and applied work.